Surgeons and ethical challenges in operating room - Syed Muhammad Nazim; Syed Shahabuddin (Journal of the Pakistan Medical Association, 2022)
Ethics lie in the heart of professionalism. In surgery, it represents an essential element, with surgeons facing ethical challenges in their routine practice. The rapid expansion of surgical technology and innovation along with the use of resources and consideration of conflict of interest have brought up the need for the development of current surgical code of ethics. Operating room represents a stressful environment where patients' lives depend upon careful preparation, planning and execution. The progression of surgery within the operating room must be done in harmony and in line with the ethical principles of autonomy, beneficence, non-maleficence and justice. Discussion of ethical problems arising in the operating room is not a common subject in surgical literature. The current narrative review was planned to cover ethical concerns related to patients' safety and privacy in the operating room and some of the evolving topics, Continuous...